(untitled) (Journal of Comparative Social Work, 2023)
The aim of this article is to reflect on the strengths and challenges in qualitative comparative research on personal social services. The specific methodological approach that these reflections emerge from is the application of case vignettes in focus group interviews with social workers, working in different welfare regimes. We describe the process of vignette construction and implementation in focus group interviews, and relate this to findings in a large international project with researchers and data from Chile, Mexico, Norway, Sweden, Lithuania, Bulgaria, Ireland and the UK. Findings reveal that some globally spread professional norms prevail when they are applied locally, while others are more formed through welfare systems with strong contextual norms and legal and socio-economic barriers. Furthermore, the project showed that to use case vignettes and focus groups, in order to compare ‘social work’ in its totality between countries, is really difficult. It appears more fruitful to use such research methods to compare subsectors and sub-disciplines instead of social work as a whole. The strength of the data retrieved from the study is that it makes it possible to separate information on actual practice from information on principles and system norms, thus providing in-practice and on-practice reflections.